Eco-City Planning; concepts and contemporary models - Hülya Coskun (Global Journal of Ecology - Peertechz Publications, 2023)
This research is specifically centered on the concepts and contemporary models of eco-city planning. In the current era, there is a notable emergence of innovative city models with a focus on addressing climate-related issues. The drive to create new urban forms and models that concentrate global warming and climate challenges has resulted in the development of contemporary and innovative models, prominently exemplified by the eco-city. Previous studies have underscored the technological, socio-economic, and political aspects of eco-cities. While eco-cities are recognized for their highly technologically innovative approaches, the development of new architectural concept considered a crucial aspect of their design. Beyond technological development, there is a significant emphasis on developing an architectural concept that considers climatic adaptation and sustainability features within a holistic approach. Therefore, the importance of crafting a technologically advanced city conducive to eco-city planning dynamics, especially with a sustainable architectural concept, is highlighted and deemed worthy of research exploration. The study delves into different contemporary eco-city models from diverse climatic regions worldwide to examine their architectural concept development challenges. Notable examples on a global scale, such as the Sino-Singaporean Tianjin Eco-city in China, Masdar City in the United Arab Emirates, and the proposed Istanbul Küçükçekmece Eco-city in Türkiye, are scrutinized. The findings of the research underscore the significance of eco-cities in terms of architectural design and the use of sustainable materials for both sustainability and climate adaptation. These models, which align with technological advancements, emerge as sustainable and climate-sensitive city models. They serve as crucial examples in developing a more sustainable architectural model. Ultimately, the research emphasizes that designing a contemporary eco-city that addresses climatic privileges and without an sustainable architectural concept will not yield a sufficiently effective result.